2010
DOI: 10.1159/000319026
|View full text |Cite
|
Sign up to set email alerts
|

CT Perfusion with Angiography as a Substitute for both Conventional Digital Subtraction Angiography and Acetazolamide-Challenged SPECT in the Follow-Up of Postbypass Patients

Abstract: Background: We evaluated the clinical usefulness of CT perfusion (CTP) with angiography (CTA) as an alternative to digital subtraction angiography (DSA) and acetazolamide (ACZ)-challenged single-photon emission computed tomography (SPECT) in the follow-up evaluation of hemodynamic changes and bypass patency after bypass surgery in chronic cerebral ischemic diseases. Methods: Thirty-five patients who underwent superficial temporal artery/middle cerebral artery bypass surgery for chronic cerebral ischemic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…They concluded that MTT is the most predictive parameter for assessing decreased CVR. Park et al [21] reported that MTT showed the best correlation with CVR of 99m Tc-HMPAO SPECT in patients with chronic cerebral ischemic disease. Eicker 136 et al [22] showed that all patients with impaired CVR proven by 99m Tc-HMPAO SPECT had delayed MTT and delayed T max in patients with ICA occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that MTT is the most predictive parameter for assessing decreased CVR. Park et al [21] reported that MTT showed the best correlation with CVR of 99m Tc-HMPAO SPECT in patients with chronic cerebral ischemic disease. Eicker 136 et al [22] showed that all patients with impaired CVR proven by 99m Tc-HMPAO SPECT had delayed MTT and delayed T max in patients with ICA occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme cerebral vasodilatation (larger than 1.2-fold) disrupts the blood-brain barrier causing vasogenic edema to develop [26,27]. Carotid revascularization reduces the collateralization demand thereby normalizing asymmetry of the rCBV and preventing the development of transient vasogenic edema [28]. Notably, the transience of the vasogenic edema suggests that edema contributes to the magnitude of the ‘LA’ score as calculated from FLAIR maps (but not as calculated from DWI maps) [29].…”
Section: Discussionmentioning
confidence: 99%
“…High recanalisation rates and good functional outcomes can be achieved by administering combined intravascular and systemic thrombolysis, using perfusion CT to select patients [19]. It can be used to assess tissue status after interventions for chronic cerebral ischaemia [20]. Multimodal CT-assisted thrombolysis may help improve functional outcomes, both within and outside the 3-hour time window, particularly beyond 3 h [21].…”
Section: Introductionmentioning
confidence: 99%